Analisis Kebijakan Pengalihan Pengelolaan SMA/SMK Oleh Dinas Pendidikan Dan Kebudayaan Provinsi Bengkulu - Anggrayni Saputri, Widya; Nur Sasongko , Rambat (Manajer Pendididikan, 2023)
The aim of this research was to describe and to analyze the diversion of policy of senior and vocational high school by department of education and culture at Bengkulu province. This was a descriptive quantitative research and the data were collected through interview, observation, and documentation. The results of this research showed that since the diversion of senior high and vocational high school authority management from district and municipality government to Bengkulu province government has been done. This diversion authority policy gave significant effects to honorary teachers and temporary government workers from district and municipality government to Bengkulu province government. The supporting effects were required such as sufficient funds and equipment, and also the obstacle factors were the lack of personnel in the education and culture department at Bengkulu province. Needed to be recommended were the increasing of service of administration by empowering the function of education and culture sub-units and an intensively coordination among schools and education and culture sub units with its education and culture expert unit